ANALISIS PENGARUH PENGGUNAAN DANA ZAKAT TERHADAP PEMBERDAYAAN MASYARAKAT Studi pada Badan Amil Zakat dan Lembaga Amil Zakat di Yogyakarta - Ufi Nida Ussolikhah; Khusnul Hidayah (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2014)
This research explains the problem whether the used of zakat funds against Badan Amil Zakat and Lembaga Amil Zakat in Yogyakarta have effect toward society empowerment. This research aim is to obtain empirical evidence of the effect of using zakat fund in Badan Amil Zakat and Lembaga Amil Zakat in Yogyakarta. The data used in this research is primary data. The sampling technique is purposive sampling. Whereas, the method used to gather data is interview and questionnaire. The data were analyzed using validity test, reliability test, classical assumption test and regression test. The result of this research were processed usig SPSS program version 16 for windows indicate the effect of using zakat funds towards society empowerment. It obtained Y =20,089 + 1,294 Y as regression equation. Based on regression equation, the independent variable will change 1,294 for each change in unit of independent variable. In the conclusion, the variable of used zakat fund has an effect toward society empowerment.